2016
DOI: 10.1021/acs.est.5b04536
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolytic Temperature Dependent and Ash Catalyzed Formation of Sludge Char with Ultra-High Adsorption to 1-Naphthol

Abstract: Massively produced sewage sludge brings a serious problem to environment. Pyrolysis is a promising and bifunctional technology to dispose the sewage sludge and recover energy, in which a large amount of pyrolytic sludge char is also produced. In this study, we proposed a value-added utilization of sludge char. We prepared an adsorbent with ultrahigh capacity for hydrophobic organic pollutant (1-naphthol) by pyrolysis of sludge and removal of the ash moiety from the sludge char. The adsorptive behavior of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(37 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…In addition, the sorption rates also exhibited a transitional process: from fast to slow and then to fast due to the changes of the organic components from aliphatic to aromatic (Chen et al 2012b). With regards to the inorganic components, it was found that ash has a catalytic effect on the formation of biochar with more orderly graphitic structures in the pyrolysis process; in addition, deashing after pyrolysis increased the hydrophobic sorption sites which favored the sorption of hydrophobic organic contaminants (Liu et al 2016;Sun et al 2013). For acidic SO 2 removal, the inorganic fractions like CaCO 3 and Ca 3 (PO 4 ) 2 in biochar can transform sorbed SO 2 into new inorganic precipitations (Xu et al 2016).…”
Section: Sorption Of Biocharmentioning
confidence: 99%
“…In addition, the sorption rates also exhibited a transitional process: from fast to slow and then to fast due to the changes of the organic components from aliphatic to aromatic (Chen et al 2012b). With regards to the inorganic components, it was found that ash has a catalytic effect on the formation of biochar with more orderly graphitic structures in the pyrolysis process; in addition, deashing after pyrolysis increased the hydrophobic sorption sites which favored the sorption of hydrophobic organic contaminants (Liu et al 2016;Sun et al 2013). For acidic SO 2 removal, the inorganic fractions like CaCO 3 and Ca 3 (PO 4 ) 2 in biochar can transform sorbed SO 2 into new inorganic precipitations (Xu et al 2016).…”
Section: Sorption Of Biocharmentioning
confidence: 99%
“…have a strong effect on their sorptive capacities (Jiang & Wang, 2016;Fang et al, 2013;Xiao et al, 2014).…”
Section: Changes In Biochar Properties With Changing Pyrolysis Tempermentioning
confidence: 99%
“…For instance, Oleszczuk et al [9] dosed biochar into activated sludge and found that biochar decreased the phytotoxicity of sludge and positively affected seed germination. In addition, the variations of sludge properties caused by biochar addition may facilitate the separation and post-treatment of excess sludge by improving sludge settling property and increasing the heating value of dehydrated sludge [10,11]. Although the investigations on the improvement of sludge settling property by addition of activated carbon have been reported [2,12], the improvement of settleability of sludge by biochar addition has not been found.…”
Section: Introductionmentioning
confidence: 99%